Research advances in intramuscular fat deposition and chicken meat quality: genetics and nutrition - Jianlou Song; Zengpeng Lv; Yuming Guo (Journal of Animal Science and Biotechnology)
Abstract Chicken meat quality directly influences consumer acceptability and is crucial for the economic success of the poultry industry. Genetics and nutrition are key determinants of the meat quality traits in broilers. This review summarizes the research advances in this field, with a focus on the genetic and nutritional foundations that regulate intramuscular fat (IMF) deposition and meat quality in chickens over the past decade. The effects of embryonic nutrition, both maternal nutrition and in ovo feeding (IOF), on skeletal muscle development, the IMF content, and meat quality traits in broilers are also discussed. In genetics, single-cell RNA sequencing revealed that de novo lipogenesis predominantly occurs in myocytes, which is key to the formation of IMF in chicken muscle tissue. Fatty acid synthase (FASN) is the key enzyme involved in this process. This discovery has reshaped the traditional understanding of intramuscular lipid metabolism in poultry. Key genes, proteins, and pathways, such as FASN, FABP4, PPARG, C/EBPα, SLC27A1; LPL, APOA1, COL1A1; PPAR and ECM–receptor interactions signaling, have been identified to regulate IMF content and distribution by modulating fatty acid metabolism and adipogenesis. LncHLFF was innovatively found to promote ectopic IMF deposition in chickens via exosome-mediated mechanisms without affecting abdominal fat deposition. MiR-27b-3p and miR-128-3p were found to inhibit adipogenic differentiation by targeting PPARG, thereby affecting IMF formation. In nutrition, nutrigenomics research has shown that fructose enhances IMF deposition by activating ChREBP, providing new targets for nutritional interventions. Adjusting dietary components, including energy, protein, amino acids, fatty acids, and phytochemicals (e.g., rutin), has been shown to significantly improve meat quality in broilers. Maternal nutrition (e.g., intake of energy, amino acids, vitamins, and trace elements) and IOF (e.g., N-carbamylglutamate) have also been confirmed to significantly impact offspring meat quality, opening new avenues for improving embryonic nutrition. Based on these significant advancements, this review proposes strategies that integrate genetic and nutritional approaches. These strategies aim to modulate the differentiation fate of paraxial mesenchymal stem cells toward myogenic or adipogenic lineages and the interaction between muscle and adipose tissues. These insights would help to improve meat quality while ensuring the growth performance of broiler chickens. Graphical Abstract